Pengaruh peran orangtua terhadap debris index score siswa inklusi SDN Pakis VIII Surabaya Tahun 2020 - Nurizza, Efa; Isnanto, Isnanto; Purwaningsih, Endang (Poltekkes Kemenkes Yogyakarta, 2020)
Dental health is a part of overall health. The dental hygiene of a person can be known from the examination of the debris index score. Based on the results of a preliminary study on 20 parents of inclusion students of SDN Pakis VIII Surabaya, it is known that parents who have no role in assisting children when brushing their teeth routinely 2 times a day morning and night are as much as 90%. The results of the dental examination of 20 inclusion students at SDN Pakis VIII Surabaya found that the status of the inclusion student index debris was in poor criteria, 70%. Therefore, parents have a very big role on children's debris index scores. The problem in this study is the lack of the role of parents in children when brushing their teeth so that it affects the debris index. This research is to find out the influence of the role of parents on the debris index score of inclusive students at SDN Pakis VIII Surabaya. This type of research is a cross sectional analytic study with 60 students (dependent variable) and 60 parents (independent variables) of respondents. Data collection methods used were examination of debris index scores and interviews with parents of students. The data analysis technique uses the Spearman Somers' Gamma test. In this study shows that there is an influence of the role of parents on the debris index score of inclusion students of SDN Pakis VIII Surabaya in 2020.